Malawi Malaria Communication Strategy - Malawi Government: Ministry of Health (Malawi Government, 2021)
Malaria remains a leading cause of morbidity and mortality in Malawi majorly affecting children below five years of age and pregnant women. While this remains the case, the Government of Malawi is scaling up interventions aimed at controlling this situation through increasing access to malaria control intervention that include: the distribution of Long Lasting Insecticide treated Nets (LLINs), scaling up indoor residual house spraying (IRS) in selected districts, promoting the prevention of malaria during pregnancy through Intermittent Presumptive Treatment of malaria in pregnancy (IPTp) and increasing access to prompt diagnosis and effective malaria treatment at facility level. Recent studies have gathered evidence that despite the provision of these services, utilization of the same has not been optimum hence malaria continues to remain a problem in the country. It is in recognition of this that the Malawi’s Ministry of Health through the National Malaria Control Program has continued to invest in public information and education through the development of the Malaria Communication Strategy. The first generation of the communication strategy ended in 2014 giving rise to the review and re-writing of this second generation of the communication strategy for the period 2015 – 2020. The communication strategy is a guiding document for all partners to implement a unified and cohesive communication plan and allow for complementing programs among partners. The main focus of the strategy is to create social and behaviour change by examining barriers as to why individuals and communities are not adopting actions and behaviour that contribute to the prevention and treatment of malaria. Through this approach, we are able to devise innovative communication approaches to tackle the barriers. I am honoured that the Ministry of Health through the National Malaria Control Program recognized the need for consistency and coordination among partners implementing malaria behaviour change communication programs and involved them in the process of review and re-writing of this communication strategy. It is my belief that the strategy will play a critical role in increasing knowledge, attitude and practices towards malaria prevention and treatment and supporting our vision where “All people in Malawi are free from the burden of malaria”.